The standard for program management (Project Management Institute, Inc., 2024)
"The Standard for Program Management - Fifth Edition identifies program management principles and performance domains and provides guidance on the principles of program management that guide the behaviors and actions of organizations, professionals, and stakeholders who work on or are engaged with programs. The standard provides generally accepted definitions of programs and program management as well as concepts important to their success: program management principles, performance domains, the program life cycle, practices, and supporting activities and tools. This fifth edition of The Standard for Program Management expands and clarifies concepts presented in previous editions. It complements and aligns with the Project Management Institute's (PMI) core foundational standards and guidance documents"-- Provided by publisher.
Keywords: Project management -- Standards.; elektronické knihy; electronic books